Insomnia symptoms in children and adolescents: screening for sleep problems with the two-item Sleep Condition Indicator (SCI-02) - Illingworth, G; Mansfield, KL; Skripkauskaite, S; Fazel, M; Waite, F (BioMed Central, 2024)
Background: Sleep problems are common in young people. Yet brief screening measures to identify those most in need of an intervention are lacking. This study investigated the potential of the two-item Sleep Condition Indicator (SCI-02) for screening insomnia symptoms in children and adolescents. We sought to establish whether there are distinct subgroups with different sleep profiles and whether subgroup membership varied with gender and school year group. Methods: Students (school years 5–13; typical age 9–18 years) in England completed the OxWell Student Survey in 2021. Sleep measures included: SCI-02, sleep onset latency (SOL), sleep duration, daytime sleepiness, and worry disrupting sleep. Latent profile analysis and multinomial logistic regression explored sleep profiles and predicted class membership. Results: In total, 29,304 participants answered sleep items. Of these, 95% provided binary gender (n = 27,802, 55% female) for analyses. Five sleep profiles emerged. The profiles, labelled “good”, “moderate”, or “poor” sleepers, vary by sleep quality – which includes time taken to fall asleep (SOL), amount of sleep (sleep duration), and the disruption of sleep due to worry. The profiles are then further differentiated by high levels of daytime sleepiness – labelled “sleepy”. “Good Sleepers” (18,355, 66%), “Moderate Sleepers” (4825, 17.4%), “Moderate Sleepy Sleepers” (1250, 4.5%), “Poor Sleepers” (1037, 3.7%) and “Poor Sleepy Sleepers” (2335, 8.4%). Probable insomnia rates (SCI-02 ≤ 2) were high in both poor sleeper profiles (70–80%) compared with other profiles (0%) and the sample overall (9%). Compared with “Good Sleepers”, all other profiles were mostly female. Daytime sleepiness – the defining characteristic of the sleepy sleeper profiles – was more common in secondary school participants than primary school. Conclusions: The SCI-02 is an efficient, two-question measure to screen for potential sleep problems in young people. Sleep disruption was high: one in ten were experiencing poor sleep. Females and adolescents appeared more vulnerable to poor sleep and daytime sleepiness. The SCI-02 has the potential for use in school and community contexts to identify children and adolescents who may benefit from support managing their sleep.